The naga awakens : growth and change in Southeast Asia - Kong, Lily; Savage, Victor R.; Neville, R. J. Warwick (Times Academic Press, 1998)
Using the Southeast Asian regional landscape as its area of enquiry, the book addresses a wide range of issues that countries in the region face as they move towards the 21st century.